2015
DOI: 10.1007/s00213-015-4087-7
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants normalize elevated Toll-like receptor profile in major depressive disorder

Abstract: Rationale Abnormalities in Toll-like receptor (TLR) expression in depression have been inferred in part from observed increases in TLR4 levels in peripheral blood mononuclear cells (PBMCs) and postmortem brains of depressed and suicidal patients. Our previous study found differences in the TLR expression in PBMCs between healthy controls and patients with major depressive disorder. Normalization of increased TLR4 in PBMCs by cognitive behavior psychotherapy has been reported. However, the effects of antidepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 48 publications
4
61
3
2
Order By: Relevance
“…The labeled fraction containing CD14 + monocytes was immediately stored at 80°C for further analysis. The protocol and primers used for mRNA analyses were the same as those used in our previous studies [19, 24]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The labeled fraction containing CD14 + monocytes was immediately stored at 80°C for further analysis. The protocol and primers used for mRNA analyses were the same as those used in our previous studies [19, 24]. …”
Section: Methodsmentioning
confidence: 99%
“…Recent studies reported a significant association between TLR expression and mood disorder [19-21]. Postmodern study has shown that the protein and mRNA expression of TLRs are increased in the prefrontal cortex of adult depressed suicide victims [22].…”
Section: Introductionmentioning
confidence: 99%
“…17-5442-02; GE) density gradient centrifugation and stored at –80°C. The protocols for RNA preparation, cDNA synthesis, and mRNA analysis have been described [16]. Real-time quantitative reverse transcriptase PCR was performed using primers for human TNFAIP3 (forward, 5′-GGA CTT TGC GAA AGG ATC G-3′; reverse, 5′-TCA CAG CTT TCC GCA TAT TG-3′).…”
Section: Methodsmentioning
confidence: 99%
“…In rodents, a recent study adds significantly to the evidence that both peripheral and brain region-specific increases in tumour necrosis factor alpha lead to both sickness and depression- and anxiety disorder-relevant behavior and do so via different pathways [79]. Abnormalities in Toll-like receptor expression (TLR1-9) in depression have been observed in peripheral blood mononuclear cells and postmortem brains of depressed and suicidal patients [80]. The expression of TLR3, TLR4, TLR5, TLR7, TLR8 and TLR9 is elevated in depressed patients and antidepressant treatment completely normalizes TLR3, TLR5, TLR7, TLR8 and TLR9 levels, whereas TLR1, TLR2, TLR4, and TLR6 are decreased to below normal levels [75].…”
Section: Treat Inflammation In Depressionmentioning
confidence: 99%